1993
DOI: 10.2337/diab.42.2.288
|View full text |Cite
|
Sign up to set email alerts
|

Early Exposure to Cow's Milk and Solid Foods in Infancy, Genetic Predisposition, and Risk of IDDM

Abstract: Using a case-control study design, we examined the hypothesis that early exposure to cow's milk and solid foods increased the risk of IDDM. An infant diet history was collected from 164 IDDM subjects from the Colorado IDDM Registry with a mean birth year of 1973, and 145 nondiabetic population control subjects who were frequency matched to diabetic subjects on age, sex, and ethnicity. Early exposure was defined as exposure occurring before 3 mo of age. After controlling for ethnicity, birth order, and family i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(47 citation statements)
references
References 25 publications
1
46
0
Order By: Relevance
“…32 Evidence for prevention of inflammatory bowel diseases (IBD) is inconclusive, with studies showing that breastfeeding reduces 33 or increases the risk for the development of IBD. 34 Exposure to beneficial components in HM that promote the development of the immune system, a lack of exposure to stimuli that would trigger an inappropriate immunologic response in genetically predisposed individuals, or both have been proposed as mechanisms underlying the reduced risk of developing autoimmune diseases, 35 although the relative contributions of these 2 effects are unknown. Further research is needed in this area, particularly in elucidating the interaction between host genetics and breastfeeding in modulating the risk of IBD.…”
mentioning
confidence: 99%
“…32 Evidence for prevention of inflammatory bowel diseases (IBD) is inconclusive, with studies showing that breastfeeding reduces 33 or increases the risk for the development of IBD. 34 Exposure to beneficial components in HM that promote the development of the immune system, a lack of exposure to stimuli that would trigger an inappropriate immunologic response in genetically predisposed individuals, or both have been proposed as mechanisms underlying the reduced risk of developing autoimmune diseases, 35 although the relative contributions of these 2 effects are unknown. Further research is needed in this area, particularly in elucidating the interaction between host genetics and breastfeeding in modulating the risk of IBD.…”
mentioning
confidence: 99%
“…Although a number of studies suggested a correlation between the incidence of childhood IDDM and some isolated putative risk determinants, such as coffee consumption by the mother (1) sugar consumption (2), cow's milk (3)(4)(5)(6) and viral infection (for review see (7)), there are very few studies in which the complexity of the environmental risk factors or triggers have been studied with a modern epidemiological approach (8-13). As pancreatic beta-cell destruction may begin many years before the clinical symptoms of diabetes (14), putative environmental risk factors may be operative during the whole lifespan of diabetic children, including intrauterine life.…”
mentioning
confidence: 99%
“…Migrant studies typically report migrant death rates that fall between the region of birth and region of residence at time of death (Gerber and Madhavan, 1980;Hull, 1979;Kostraba et al, 1993). We compared the death rates of the Southern-born populations in the Northeast, Midwest, and West with the region-born populations.…”
Section: Discussionmentioning
confidence: 99%